Tindak Pidana Kekerasan Dalam Rumah Tangga yang Mengakibatkan Kematian (Studi pada Polresta Pulau Ambon dan Pulau-Pulau Lease) - Hendrina Wahju Irianty Munthalib; Elsa Rina Maya Toule; Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The Indonesian government has ratified Law Number 23 of 2004 concerning the elimination of domestic violence which clearly and unequivocally regulates sanctions for perpetrators of acts of domestic violence, household that resulted in the strongest death in the jurisdiction of the Ambon Island Police and Lease Islands.Purposes of the Research: To examine and discuss the factors that influence domestic violence crimes that result in death, and the efforts that can be taken to prevent domestic violence resulting in death.Methods of the Research: This research is a normative juridical research, the type of research is descriptive normative, the type of research is descriptive analytical, the sources of legal materials used in this research are primary legal materials, secondary legal materials, supporting data and information then identified and then systematized for interpretation and given arguments to reach conclusions.Results of the Research: The results obtained from this study are the factors that influence the crime of domestic violence that results in death are individual factors, communication, patriarchal culture and the economy while the efforts made to prevent domestic violence that result in death have been carried out by The Ambon Island Police and Leasa Islands are a community service unit that collaborates with relevant agencies in the form of counseling.